Seven summers - Toon, Paige, 1975- (G. P. Putnam's Sons, 2024)
"Liv and Finn meet six summers ago working in a bar on the rugged Cornish coastline, their futures full of promise. When a night of passion ends in devastating tragedy they are bound together inextricably. But Finn's life is in LA with his band, and Liv's is in Cornwall with her family - so they make a promise. Finn will return every year, and if they are single they will spend the summer together. This summer Liv crosses paths with Tom - a mysterious new arrival in her hometown. As the wildflowers and heather come into bloom, they find themselves falling for one another. For the first time Liv can imagine a world where her heart isn't broken every autumn. Now Liv must make an impossible choice. And when she discovers the shocking reason that Tom has left home, she'll need to trust her heart even more."--